Employee Performance: Exploring the Nexus of Nonstandard Services, Psychological Contracts, and Knowledge Sharing - Ahmad Munawir; Bambang Dwi Suseno (Human Behavior and Emerging Technologies)
Contribution: Overall, these findings highlight the intertwined roles of psychological contracts, knowledge sharing, and nonstandard services in shaping employee behavior and improving organizational outcomes. By prioritizing these elements, organizations can foster a culture of engagement, innovation, and high performance, leading to sustained organizational effectiveness and success. The research findings underscore the critical importance of strategic management of psychological contracts in shaping employee behaviors and organizational outcomes. Establishing positive psychological contracts can enhance employee engagement and commitment, ultimately leading to organizational success. Future research endeavors should consider exploring the longitudinal effects of psychological contracts, knowledge sharing practices, and nonstandard services on organizational outcomes. Longitudinal studies offer the opportunity to observe how these factors evolve over time and their enduring impact on organizational effectiveness.